SELF-CARE PRACTICES OF ELDER PATIENTS UNDERGOING DIALYTIC TREATMENT - Débora Regina de Oliveira; Fernanda Spiel Tuoto; Maria Helena Lenardt (Universidade Federal do Paraná, 2000)
Descriptive exploratory study with elder chronic renal patients attending hemodyalisis sessions in a School Hospital in the city of Curitiba/ Brazil, whose goal was to elucidate self-care practices of these elder patients undergoing dialytic treatment. The study was theoretically grounded by Foucault (1985). Data collection was carried out through an interview formulary with questions related to identification and self-care. Data evidenced the following: age ranged 65 and 75 years; 47% have not finished elementary school and 23% are illiterate; hemodialysis timespan ranged one month to 3 years; 23. 5% pointed out difficulties to move over and 17.6% pointed out financial problems as hindrances for better self-care. Self-care ways evidenced: 41% partially diet, not being able to follow up nutriotionist's prescribed diet; 17.6% do not perform heavy physical activities; 20% of the patients still unfolded that praying is a way of self-care. Based on this research results, the authors suggest that care counselling effected by the nursing team to elder patients must be adapted to practice in order to significantly influence elder renal chronic patients' self-care reality.